Kualitas Sumber Daya Manusia terhadap Kinerja Aparatur Sipil Negara dalam Mendukung Pembangunan dan Pengembangan Kota Probolinggo - Eko Wicaksono (Journal on Education, 2022)
The current problem shows that the human resources of the existing apparatus are very far from what is expected. Therefore, it is necessary to develop the human resources of the apparatus so that they can improve the quality of the apparatus, both their professional abilities, insight abilities, leadership abilities and service abilities so that in the end it will improve the quality of work of an apparatus. This study aims to see and examine the quality of human resources that have been / are being carried out to improve the performance of Civil Servants. The quality of human resources is an analysis of activities carried out to improve and improve the knowledge and skills of employees through education and training, non-training activities, learning assignments and promotions. Then the performance of civil servants is the quality of service, timeliness, the value of the list of work implementation, attendance, and interpersonal impact. The research method used is the correlation method, which is a research process that looks at the relationship between the independent variable (X) and the dependent variable (Y). The study population was 32 civil servants at the Office of the Revenue and Financial Management and Asset Management Office of the City of Probolinggo. The research sample was taken from the entire population, amounting to 32 respondents. Meanwhile, to examine the service quality of the apparatus, which is one indicator of the apparatus' performance, the authors took a sample of 32 people. Based on the research conducted and continued with analysis using the Pearson Product Moment Correlation Coefficient (rxy) test, the result is that there is no correlation between the quality of human resources and the increase in the performance of civil servants, with the acquisition of an rxy value of -0.143 which indicates there is no relationship.